2001
DOI: 10.1007/s004030100245
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of microchimerism in systemic sclerosis skin tissue

Abstract: It has been reported that more male DNA of presumed fetal origin is present in the blood and skin of women with systemic sclerosis (SSc) as compared with healthy controls after delivery, but these findings are controversial. We sought to determine whether male cell DNA is present in SSc using a quantitative polymerase chain reaction for Y chromosome DNA. The study groups comprised 57 healthy women, 49 patients with SSc and 30 patients with connective tissue diseases other than SSc who had given birth to at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
0
22
0
5
Order By: Relevance
“…Cases and controls from the selected studies were assessed for our inclusion/exclusion criteria. Eleven of 35 studies had subjects meeting the inclusion criteria (7,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21). Individual data from 124 of 447 study subjects were extracted from these 11 studies and analyzed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases and controls from the selected studies were assessed for our inclusion/exclusion criteria. Eleven of 35 studies had subjects meeting the inclusion criteria (7,(11)(12)(13)(15)(16)(17)(18)(19)(20)(21). Individual data from 124 of 447 study subjects were extracted from these 11 studies and analyzed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in two of the studies (16,20), detailed pregnancy information was available only for subjects with autoimmune disease and detectable microchimerism. Therefore, in the current study, the observed association between microchimerism and autoimmune disease is biased.…”
Section: Discussionmentioning
confidence: 99%
“…An important observation that arose from studies of fetal microchimerism in systemic sclerosis was that the simple presence of microchimerism is common in healthy individuals, and quantitative techniques are important in the comparison of patients to controls (10,11). Whereas male DNA can be quantified in women who gave birth to sons as a measure of fetal microchimerism, another approach was needed for MMc.…”
Section: Maternal Cells Have Recently Been Found In the Circulation Amentioning
confidence: 99%
“…This is in accordance with the fact that several studies have not found any association with the presence of FMc. In SSc skin tissue, 29% of women affected with SSc compared with 35% of healthy women presented fetal cells (Gannage et al 2002;Ohtsuka et al 2001). In primary biliary cirrhosis, authors did not find any significant differences when they compared affected and healthy women (Corpechot et al 2000;Fanning et al 2000;Tanaka et al 1999).…”
Section: Immune Reactions Triggered By Fetal Microchimeric Cellsmentioning
confidence: 79%